2018
DOI: 10.1159/000492580
|View full text |Cite
|
Sign up to set email alerts
|

Mismatch Repair Deficiency Drives Durable Complete Remission by Targeting Programmed Death Receptor 1 in a Metastatic Luminal Breast Cancer Patient

Abstract: Background: In the field of breast cancer tumor biology, triple-negative breast cancer patients are the main focus of current clinical trials exploring the use of immune checkpoint inhibitors due to higher frequencies of somatic mutations, neoantigens, and resulting tumor-specific T-cell reactivity. Case Report: Here, we present the case of a 66-year-old woman with metastatic luminal breast cancer that rapidly responded to monotherapy with pembrolizumab, a monoclonal anti-PD-1 antibody. This patient obtained a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 40 publications
0
12
0
Order By: Relevance
“…Using our assay, we identified 31 MMR-deficient cases out of 1635 that had data for all four MMR biomarkers (MSH2, MSH6, MLH1 and PMS2). Despite its relative rarity in breast cancer, this population is important as MMR-deficient cancers have been highly responsive to immune therapies such as PD-1 or CDK4/6 checkpoint inhibitors [1,13,[33][34][35]. The 1.9% frequency of MMR deficiency in our study corroborates well with the genomic findings reported from the Sanger Centre, who on the basis of mutational signatures derived from whole genome sequencing of 640 cases, identified 11 cases (1.7%) as MMR-deficient [19].…”
Section: Discussionmentioning
confidence: 99%
“…Using our assay, we identified 31 MMR-deficient cases out of 1635 that had data for all four MMR biomarkers (MSH2, MSH6, MLH1 and PMS2). Despite its relative rarity in breast cancer, this population is important as MMR-deficient cancers have been highly responsive to immune therapies such as PD-1 or CDK4/6 checkpoint inhibitors [1,13,[33][34][35]. The 1.9% frequency of MMR deficiency in our study corroborates well with the genomic findings reported from the Sanger Centre, who on the basis of mutational signatures derived from whole genome sequencing of 640 cases, identified 11 cases (1.7%) as MMR-deficient [19].…”
Section: Discussionmentioning
confidence: 99%
“…Previous study [ 47 ] analyzed 1861 advanced melanoma patients and showed that anti-CTLA4 antibody (ipilimumab) could greatly prolong patients' long-term survival. Recently, anti-PD1 antibody (nivolumab) has been found to be ineffective against metastatic renal cell carcinoma, advanced squamous cell carcinoma, non-small-cell lung cancer, melanoma, or luminal-like breast cancer [ 48 , 49 ]. Therefore, there is a need for developing novel biomarkers predictive of whether cancer patients could benefit from checkpoint immunotherapy.…”
Section: Discussionmentioning
confidence: 99%
“…A recent study demonstrated that dMMR can be used as a prognostic and likely predictive biomarker, but without being interchangeable with MSI as in other tumor types [98]. Additionally, a case study of a woman with metastatic, ER + , HER2breast cancer, showed durable complete remission after treatment with pembrolizumab [102]. Although dMMR cases are infrequent in breast cancer, there is an urgent need to identify and select even that fairly low proportion of patients who could benefit from immunotherapy.…”
Section: Mismatch Repair and Microsatellite Instabilitymentioning
confidence: 99%